Performance of Dual-Media Down-Flow Rapid Gravity Filters - I. Abdul-Wahab, Majid; N. AI-Ghanim, Nada; H. Essebbag, Baseem (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The present study was conducted to evaluate the effect of variation of influent raw water turbidity, bed composition, and filtration rate on the performance of mono (sand) and dual media (sand and anthracite) rapid gravity filters in response to the effluent filtered water turbidity and headloss development. In order to evaluate each filter pe1formance, sieve analysis was made to characterize both media and to determine the effective size and uniformity coefficient. Effluent filtered water turbidity and the headloss development was recorded with time during each experiment.